Amalan jawatankuasa keselamatan dan kesihatan pekerja melalui konsep penyertaan pekerja: kajian kes di kilang sawit LM Sandakan, Sabah, Malaysia - Balakrishnan Parasuraman; Irma Wani Othman; Fadilah Syahirah Jurup; Balan Rathakrishnan (Department of Southeast Asian Studies, UM, 2017)
This research focuses on the practices of Safety and Health Workers Committee (JKKP) through employee participation in Kelapa Sawit LM factory, Sandakan, Sabah. The research focuses mainly on two groups of informants representing management and the workers involved in JKKP pratices. This research uses a qualitative method to collect data from the respondents. About 13 informants were interviewed (6 representing management and 7 representing employee). Observations on the meeting and documents from 2001 until 2006 are used to support findings from the inverviews. The results indicate that JKKP in the Kilang Kelapa Sawit LM gives impotance to the employee’s participation in solving issues on safety and health among workers. The research finding is similar to model created by Joint Consultation Committee of Marchington which is also applicable to that of Kelapa Sawit LM factory, Sandakan, Sabah